Development and Verification of Novel Building Integrated Thermal Storage System Models - Matthias Pazold; Jan Radon; Matthias Kersken; Hartwig Künzel; Florian Antretter; Herbert Sinnesbichler (Energies, 2023)
In electrical grids with a high renewable percentage, weather conditions have a greater impact on power generation. This can lead to the overproduction of electricity during periods of substantial wind power generation, resulting in shutoffs of wind turbines. To reduce such shutoffs and to bridge periods of lower electricity production, three thermal energy storage systems (TESs) have been developed for space heating and domestic hot water. These include a water-based thermal system (WBTS), a thermally activated building system (TABS), and a high-temperature stone storage system (HTSS). The paper explains the development of computer models used to simulate the systems and their successful verification using field measurements. Target values to cover about 90% of building heating demand with excess electricity were found to be achievable, with performance ratios depending on storage size, particularly for WBTS and HTSS. The TABS’ storage capacity is limited by building geometry and the available inner ceilings and walls.